PHYSICAL AND ENVIRONMENTAL MONITORING OF AIR ON CMW - Galina Khamzatovna Badakhova; Nelly Anatolievna Kravchenko; Olga Grigoryevna Fabrikantova (Современная наука и инновации)
It was made the analysis of atmosphere circulation and wind regimes in modern climate conditions, so as their influence on capacity, transfer and washing away of air contaminant in the air above Caucasus Mineral Water region